Determinasi Kepemimpinan Kepala Sekolah dan Kompetensi Guru terhadap Motivasi Belajar Siswa Kelas XI di SMK Pratama Widya Mandala Badung - I Gusti Ayu Ika Monika (Universitas Muhammadiyah Enrekang, 2021)
The purpose of this study was to determine the determination of principal leadership, teacher competence on learning motivation of class XI students at SMK PratamaWidya Mandala Badung. This research is an